Straightforward access to biocompatible poly(2-oxazoline)-coated nanomaterials by polymerization-induced self-assembly. Issue 26 (12th March 2019) - Le, Dao; Wagner, Friederike; Takamiya, Masanari; Hsiao, I-Lun; Gil Alvaradejo, Gabriela; Strähle, Uwe; Weiss, Carsten; Delaittre, Guillaume
Abstract : Poly(2-ethyl-2-oxazoline) chain transfer agents are employed in photoinitiated RAFT PISA, providing access to biocompatible core–shell polymeric nanostructures with various morphologies. Abstract : We report the synthesis of poly(2-ethyl-2-oxazoline)-based (PEtOx) nanoobjects by polymerization-induced self-assembly (PISA). First, well-defined PEtOx macromolecular chain transfer agents were synthesized by cationic ring-opening polymerization and click chemistry. The photoinitiated PISA of 2-hydroxypropyl methacrylate mediated by these PEtOx produced nanoobjects spanning the full range of core–shell morphologies. The nanoparticles exhibited high biocompatibility and stealth properties in vitro or in vivo, as well as thermoresponsive behavior.